A comprehensive technology strategy for microbial identification and contamination investigation in the sterile drug manufacturing facility—a case study - Song, Minghui; Li, Qiongqiong; Liu, Chengzhi; Wang, Peien; Qin, Feng; Zhang, Lichun; Fan, Yiling; Shao, Hong; Chen, Guiliang; Yang, Meicheng (Frontiers in Microbiology, 2024)
A comprehensive strategy for microbial identification and contamination investigation during sterile drug manufacturing was innovatively established in this study, mainly based on MALDI-TOF MS for the identification and complemented by sequencing technology on strain typing. It was implemented to monitor the bacterial contamination of a sterile drug manufacturing facility, including its bacterial distribution features and patterns. In three months, two hundred ninety-two samples were collected covering multiple critical components of raw materials, personnel, environment, and production water. Based on our strategy, the bacterial profile across the production process was determined: 241/292 bacterial identities were obtained, and Staphylococcus spp. (40.25%), Micrococcus spp. (11.20%), Bacillus spp. (8.30%), Actinobacteria spp. (5.81%), and Paenibacillus spp. (4.56%) are shown to be the most dominant microbial contaminants. With 75.8% specieslevel and 95.4% genus-level identification capability, MALDI-TOF MS was promising to be a first-line tool for environmental monitoring routine. Furthermore, to determine the source of the most frequently occurring Staphylococcus cohnii, which evidenced a widespread presence in the entire process, a more discriminating S.taphylococcus cohnii whole-genome SNP typing method was developed to track the transmission routes. Phylogenetic analysis based on SNPs results indicated critical environment contamination is highly relevant to personnel flow in this case. The strain typing results provide more robust and accurate information for the following risk assessment step and support more effective preventive and corrective measures. In general, the strategy presented in this research will facilitate the development of improved production and environmental control processes for the pharmaceutical industry, and give insights about how to provide more sound and reliable evidence for the optimization of its control program.